The Role of the Satintelkam Security Unit in Reducing the Number of Criminal Offenses of Persecution Involving Members of Pencak Silat Schools in the Jurisdiction of Surabaya Polrestabes - Wardana, Dzaky Raditya (Advances in Police Science Research Journal, 2024)
The number of persecution cases involving members of pencak silat community in Surabaya City has been increasing over the last 3 (three) years. Starting from 2021 there were 7 cases, then in 2022 there were 33 cases, and in 2023 there were 22 cases. This will certainly disturb the sense of security and comfort of the people of Surabaya if no efforts are found to reduce potential conflicts. This paper focuses on the implementation of Intelligence raising and the efforts of the Intelkam Security Unit of Polrestabes Surabaya in reducing the number of criminal acts of persecution involving members of pencak silat community in Surabaya City.             This study applies humanistic communication theory, POAC management theory, management element theory, as well as the concepts of intelligence gathering, the Intelkam Security Unit, reducing crime rates, and the concept of assault. The author also utilizes a descriptive qualitative method with data collection is conducted through observation, interviews, and document studies. Furthermore, data validity is tested using triangulation of sources, techniques, time, and theory. The results show that the implementation of raising by the Security Unit of the Intelkam Polrestabes Surabaya cannot be considered optimal due to several aspects that have not been carried out properly, including the role of raising has not been carried out at all pencak silat community, multiple task assignment that will make impact for Satintelkam members when carry on their job, the needs for renewal of raising facilities and infrastructure, also The Intelkam efforts involving other internal police functions and members of pencak silat community in carrying out the task of beheading.